OPTIMIZING APPLE’S VALUE CHAIN: A MULTIFACETED EXPLORATION OF FACTORS INFLUENCING HIGH-QUALITY AVAILABILITY IN THE MARKET - Asaad Karam (Mesopotamia Journal of Agriculture, 2025)
The present research seeks to assess Iraqi Kurdistan's apple fruit value chain, emphasizing the identification of the major stakeholders and the support services available. A non-probability sampling of 120 respondents from the value chain in Duhok City was conducted. Therefore, the respondents were well distributed regarding age, education, and occupation, making the study results more credible. Using regression analysis, it was seen that there is a high correlation between the availability of quality apples and other factors like stakeholders, input suppliers, research institutions, and financial services, as shown by R2 = 0.974. This paper highlights some challenges, including the absence of advanced cultivation practices and inadequate access to finance, which impact the quality and pricing of the products. However, the suitable climate, good soils, and many varieties of apples that grow in Kurdistan offer a potential for export development. The conclusion shows the need to address the challenges identified and build on the strengths to improve the performance of the apple fruit value chain in the Kurdistan region.